Analysis of reproductive hormones and transcriptomics in the hypothalamus and pituitary under different photoperiods - Mengqian Liu; Lei Tan; Xinlu Li; Haojie Li; Yong Zhang; Xiannian Zi; Changrong Ge; Kun Wang (Poultry Science, 2025)
This investigation aimed to use transcriptome analysis to explore the key genes and signaling pathways through which photoperiod impacts reproductive hormone secretion in roosters. 240 forty-two-day-old Chahua No.2 roosters were randomly assigned to four groups: simulated natural light (Ⅰ), 12L:12D (Ⅱ), 16L:8D (Ⅲ), and 20L:4D (Ⅳ), with 6 replicates per group and 10 roosters in each replicate. Blood samples were collected at 91 days and 140 days after hatching to measure the levels of various reproductive hormones. Subsequently, the two groups with the most significant differences in reproductive hormone levels were chosen for in-depth transcriptomic analysis. Select the two groups with the greatest differences in reproductive hormones for transcriptomic analysis. Results showed that at 90 days of age, the duration of light exposure had no significant effect on the levels of GnRH, FSH, and LH (P > 0.05); at 140 days of age, with prolonged exposure to light, the levels of GnRH, FSH, and LH in the blood will significantly or extremely significantly increase (P < 0.05). Transcriptome analysis of pituitary tissues identified 467 significantly differentially expressed genes, with 133 genes being significantly downregulated and 334 genes being significantly upregulated. Key signaling pathways identified included calcium signaling pathway, neuroactive ligand-receptor interaction. Transcriptome analysis of hypothalamus tissues identified a total of 1374 significantly differentially expressed genes, of which 693 were significantly downregulated and 681 were significantly upregulated. A significantly enriched neuroactive ligand-receptor interaction signaling pathway was identified. The results indicate that the extension of photoperiod affects the expression of genes such as ATP2A3, ATP2B1, MCU, GnRH-I, TRH in the hypothalamus and pituitary by regulating the calcium signaling pathway and the neuroactive ligand-receptor interaction, thereby regulating the secretion of GnRH, FSH, and LH.